Semantic Study of Comparative Figure of Speech in Album Entitled False Testament by Rapper DFA (DEWA) - Mochamad Daffa Ramadhika; Hero Gunawan (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This research investigates comperative figurative language used in the album entitled False Testament by rapper DFA (usually pronounced as Deva). Thus, there are two purposes this research try to conduct, first is to find out what type of comparative figurative language used in each song of the album and more after is to understanding the meaning of each comparative figurative language found in an album and use Gorys Keraf theory to identify figure of speech which taken based on characteristics and understand the meaning behind words or sentences that used figure of speech. The method use to conduct this research is descriptive research; desribed, categorized, and analyzed. After following each mentioned step, the conclusion has successfully obtained that this album do not use any form of comparative figurative language except hyperbole, personification and metaphor and the meaning of each specimen data has fully explained. Thus, for the next research, researcher are able to analyze other type of figurative language in the album entitled False Testament by DFA since there are a lot of other types of figurative language that can be use to analyze the meaning in other form of literary.